2008
DOI: 10.4028/www.scientific.net/kem.368-372.1699
|View full text |Cite
|
Sign up to set email alerts
|

Ab-Initio Study on Adsorption and Diffusion of Au Atoms on Clean Si(001) and H-Si(001) Surface

Abstract: Performing ab-initio total-energy calculations to investigate the adsorption and diffusion processes of the Au atoms with both the clean Si(001)-(1×1) and H-terminated Si(001)-(2×1) surfaces. It was found that, on the clean Si(001)-(1×1) surface, the most stable adsorption sites for Au atoms are middle part of four Si atoms, while on H-terminated Si(001)-(2×1) surface, the most stable sites are the middle part of a Si-Si dimer. The result showed that surface hydrogenation make most stable site transfer and aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
1
1
0
Order By: Relevance
“…The mechanism and rate of diffusion of a Au adatom on the reconstructed Si(100)-2 × 1 surface has been calculated using the CI-NEB method for identifying optimal diffusion paths with energy and atomic forces estimated from DFT/PBEsol. While the most stable binding site is found to be in between dimer rows, in agreement with previous theoretical calculations and STM experimental measurements [16,17], the dominant diffusion mechanism is found to involve promotion of the adatom into metastable sites on top of a dimer row and multiple hops along the row, before the adatom settles down again into an optimal binding site between dimer rows. This indirect diffusion mechanism becomes more dominant the lower is the temperature.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The mechanism and rate of diffusion of a Au adatom on the reconstructed Si(100)-2 × 1 surface has been calculated using the CI-NEB method for identifying optimal diffusion paths with energy and atomic forces estimated from DFT/PBEsol. While the most stable binding site is found to be in between dimer rows, in agreement with previous theoretical calculations and STM experimental measurements [16,17], the dominant diffusion mechanism is found to involve promotion of the adatom into metastable sites on top of a dimer row and multiple hops along the row, before the adatom settles down again into an optimal binding site between dimer rows. This indirect diffusion mechanism becomes more dominant the lower is the temperature.…”
Section: Discussionsupporting
confidence: 87%
“…An adatom initially sitting on top of a row was observed to move in between rows during STM manipulation, indicating that the latter site is more stable. Previous density functional theory (DFT) studies had reported binding sites in between the dimer rows (BDRs) [17] and there it was assumed that diffusion occurs by adatom hops between such binding sites, the adatom thereby remaining in between dimer rows during diffusion. More extensive DFT calculations by Chiaravalloti et al, however, identified also two binding sites on top of the dimer rows, an asymmetric site at the edge of the dimer row (TDR1) and a symmetric site in the center of a row (TDR2).…”
Section: Introductionmentioning
confidence: 99%